Dinuclear manganese(iii) complexes with bioinspired coordination and variable linkers showing weak exchange effects: a synthetic, structural, spectroscopic and computation study. Issue 18 (14th January 2019) - Shova, Sergiu; Vlad, Angelica; Cazacu, Maria; Krzystek, J.; Ozarowski, Andrew; Malček, Michal; Bucinsky, Lukas; Rapta, Peter; Cano, Joan; Telser, Joshua; Arion, Vladimir B.
Abstract : High-resolution HFEPR indicates weak exchange interactions between Mn III ions in agreement with DFT calculations. Abstract : Three dimanganese(iii ) complexes have been synthesised and fully characterised by standard spectroscopic methods and spectroelectrochemistry. Each Mn III ion is chelated by a salen type ligand (H2 L), but there is variation in the bridging group: LMn(OOCCHCHCOO)MnL, LMn(OOCC6 H4 COO)MnL, and LMn(OOCC6 H4 C6 H4 COO)MnL. X-ray diffraction revealed an axial compression of each six-coordinate high-spin d 4 Mn III ion, which is a Jahn–Teller-active ion. Temperature dependent magnetic susceptibility and variable temperature-variable field (VTVH) magnetisation measurements, as well as high-frequency and -field EPR (HFEPR) spectroscopy were used to accurately describe the magnetic properties of the complexes, not only the single-ion spin Hamiltonian parameters: g -values and zero-field splitting (ZFS) parameters D and E, but also the exchange interaction constant J between the two ions, which has been seldom determined for a di-Mn III complex, particularly when there is more than a single bridging atom. Quantum chemical calculations reproduced well the electronic and geometric structure of these unusual complexes, and, in particular, their electronic absorption spectra along with the spin Hamiltonian and exchange parameters.